'I didn't know what strong was until it was required': factors that promote retention among homeless students in higher education. Issue 2 (7th February 2020) - Mulrenan, Patrick; Atkins, Julia; Cox, Simon
ABSTRACT: This study examines the experience of homeless university students. A focus group and in-depth interviews were conducted among 16 homeless students at a university in London to determine the factors that enable them to remain at university despite being homeless. Homelessness has been increasing in the UK since 2010, particularly in London. Combined with the widening participation initiative, which encourages access to Higher Education formore disadvantaged communities, this means that increasing numbers of students may face homelessness during their studies. The study demonstrates considerable personal resilience among homeless students. These students find it hard to fully engage with other students, or with the wider university experience. Most were in fact too embarrassed to tell their university friends that they were homeless. Keyfactors that promoted resilience were sense of purpose, personal determination, and the relationship with their families. The critical relationship was, however, with their children. Decisions to attend and remain at university were based not on having a role model, but on the desire to provide a positive role model to their children. The study also acknowledges wider structural factors; homelessness is influenced by national and international trends outside the influence of individual and institutional actors.